A Literature Review on Antipyrinein Chemistry Fields (American International Journal of Sciences and Engineering Research, 2019)
This   literature   review   concerned   with  antipyrine  compound . Antipyrine compound   is  very  important  compound  in  many  chemistry  fields  such   as  in  coordination chemistry , analytical chemistry  as a reagent   which   continuously   identified  for possible   uses  and   applications in  several  fields   beside  to  pharmacological  , medical   and  industrial  fields.